2010
DOI: 10.1002/lapl.201010042
|View full text |Cite
|
Sign up to set email alerts
|

Diode-pumped Nd:LuVO4 and Nd:YAG crystals yellow laser at 594 nm based on intracavity sum-frequency generation

Abstract: We present for the first time laser architecture to obtain continuous-wave yellow radiation at 594 nm. The choice of crystals (Nd:LuVO4 for emission at 1343 nm and Nd:YAG for emission at 1064 nm) was guided by laser performance. A part of the pump power was then absorbed by the Nd:LuVO4 crystal, the remaining was used to pump the Nd:YAG crystal. Intracavity sum-frequency mixing at 1343 and 1064 nm was realized in a KTiOPO4 (KTP) crystal to reach the yellow radiation. We obtained a continuous-wave output power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Classical wavelengths of frequency-doubled DPSS blue lasers are 473 nm (Nd:YAG laser) [10,11], 0.46 μm (Nd:vanadate lasers) [12][13][14][15][16]. The lowest wavelengths ever reported with DPSS lasers based on Nd ions are 454 nm with Nd:YLF and 453 nm with Nd:ASL [17,18] and recently 440 nm in Nd:YVO 4 and Nd:GdVO 4 [19][20][21]. The Nd-doped Nd:CNGG crystal, which belongs to the class of Nd-doped disordered laser materials, is an attractive gain medium suitable for diode pumping [22].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Classical wavelengths of frequency-doubled DPSS blue lasers are 473 nm (Nd:YAG laser) [10,11], 0.46 μm (Nd:vanadate lasers) [12][13][14][15][16]. The lowest wavelengths ever reported with DPSS lasers based on Nd ions are 454 nm with Nd:YLF and 453 nm with Nd:ASL [17,18] and recently 440 nm in Nd:YVO 4 and Nd:GdVO 4 [19][20][21]. The Nd-doped Nd:CNGG crystal, which belongs to the class of Nd-doped disordered laser materials, is an attractive gain medium suitable for diode pumping [22].…”
Section: Introductionmentioning
confidence: 96%
“…These past few years, there has been extensive research to find more efficient and more compact lasers. Thus, new lasers were designed to reach new wavelengths, for example in the yellow range [1][2][3][4][5], or to improve sources already used, as in the blue range [6][7][8][9]. Diode-pumped solidstate (DPSS) lasers operating in the blue spectral range have a large number of applications ranging from highdensity optical data storage to phototherapy and medical diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first appearance in 2002 [3], the new vanadate laser crystal, Nd:LuVO 4 , has attracted much attention because it owns many prominent advantages including large absorption and emission cross sections, high damage threshold, and is easy to process. These properties are favorable to make high efficiency DPSSLs, and in recent years the research and application on this material have covered many areas, such as near infrared laser [11][12][13][15][16][17][18], visible laser by frequency mixing [19][20][21][22][23], Q-switched laser [13,[24][25][26][27][28][29], mode-locked laser [30][31][32][33][34][35][36][37][38], and self-Raman frequency shifting [10,39]. Nevertheless, the research of J. Morikawa et al [40] has shown that the thermal conductivity of Nd:LuVO 4 crystal is obvious lower than the other two well-known vanadate crystals, Nd:YVO 4 and Nd:GdVO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides providing remarkable non-invasive surface imaging techniques, they have demonstrated tremendous potential for numerous other applications, as in the development of coherent light sources at different frequencies. For example, SFG has been used in the production of light sources in the UV-Vis spectral range [23,24] and DFG for sources at mid or far infra-red frequencies [25][26][27]. Generation of the previously inaccessible terahertz (THz) frequency band have also been facilitated by DFG [28,29].…”
Section: Introductionmentioning
confidence: 99%